Apolar Bioactive Fraction of Melipona scutellaris Geopropolis on Streptococcus mutans Biofilm. (13th June 2013) - Cunha, Marcos Guilherme da; Franchin, Marcelo; Galvão, Lívia Câmara de Carvalho; Bueno-Silva, Bruno; Ikegaki, Masaharu; de Alencar, Severino Matias; Rosalen, Pedro Luiz
Abstract : The aim of this study was to evaluate the influence of the bioactive nonpolar fraction of geopropolis on Streptococcus mutans biofilm. The ethanolic extract of Melipona scutellaris geopropolis was subjected to a liquid-liquid partition, thus obtaining the bioactive hexane fraction (HF) possessing antimicrobial activity. The effects of HF on S. mutans UA159 biofilms generated on saliva-coated hydroxyapatite discs were analyzed by inhibition of formation, killing assay, and glycolytic pH-drop assays. Furthermore, biofilms treated with vehicle control and HF were analyzed by scanning electron microscopy (SEM). HF at 250 μ g/mL and 400 μ g/mL caused 38% and 53% reduction in the biomass of biofilm, respectively, when compared to vehicle control (P < 0.05 ) subsequently observed at SEM images, and this reduction was noticed in the amounts of extracellular alkali-soluble glucans, intracellular iodophilic polysaccharides, and proteins. In addition, the S. mutans viability (killing assay) and acid production by glycolytic pH drop were not affected (P > 0.05 ). In conclusion, the bioactive HF of geopropolis was promising to control the S. mutans biofilm formation, without affecting the microbial population but interfering with its structure by reducing the biochemical content of biofilm matrix.